Remifentanil reduces post-induction hypotension compared to fentanyl in thoracoscopic esophagectomy: a retrospective cohort study - Zhang, Jin; Zhao, Chen; Sun, Hao; Deng, Youming; Qian, Guangfu; Teng, Shibing; Wang, Baoxin (Frontiers in Pharmacology, 2025)
BackgroundPost-induction hypotension (PIH) is a common complication associated with anesthesia, particularly in high-risk groups, such as elderly, malnourished patients with multiple comorbidities undergoing thoracoscopic esophagectomy. The selection of induction agents plays a significant role in influencing hemodynamic stability. However, there is a lack of comprehensive comparative data regarding the impact of different opioid agents on PIH.MethodsThis retrospective cohort study included 289 patients undergoing thoracoscopic esophagectomy, who received etomidate combined with either fentanyl (Fentanyl group) or remifentanil (Remifentanil group) for anesthesia induction. A logistic regression model was used to examine the association between the induction regimen and PIH. Confounding factors were adjusted using a directed acyclic graph, and least absolute shrinkage and selection operator (LASSO) regression was employed to select covariates, ensuring robustness of the primary outcome analysis. Hemodynamic changes in systolic blood pressure, mean arterial pressure, and heart rate during the first 15 min post-induction were analyzed using generalized estimating equations to account for correlated observations. Subgroup analyses were performed for key clinical subgroups.ResultsAmong 289 patients analyzed, the incidence of PIH was significantly lower in the Remifentanil group compared to the Fentanyl group (23.7% vs. 42.3%, P = 0.001; adjusted odds ratio (OR) = 0.42, 95% confidence interval (CI): 0.25–0.73). Sensitivity analysis using LASSO-selected covariates yielded consistent results (adjusted OR = 0.41, 95% CI: 0.22–0.69, P = 0.001). Bradycardia occurred more frequently with remifentanil (11.9% vs. 4.5%, P = 0.03), whereas post-intubation hypertension and phenylephrine use were higher in the fentanyl group. No significant differences were observed in cardiovascular complications or postoperative hospital stay. Subgroup analyses revealed no significant effect modification across age, hemoglobin, or albumin levels. Remifentanil was also associated with more stable hemodynamics, including attenuated systolic blood pressure decline and lower variability during the first 15 min post-induction.ConclusionRemifentanil-based general anesthesia induction reduces the risk of PIH and enhances hemodynamic stability in patients undergoing thoracoscopic esophagectomy.